A influ??ncia de caracter??sticas de gest??o de projetos nos leil??es de energia solar fotovoltaica - Maleski, Stefano (2017)
For years it is perceived a demographic increase that according to predictions, in a smaller scale it must continue to exist, we also notice the exponential emergence of new technologies, also currently exists in Brazil a scenario of alteration in the demographic pyramid, in which it becomes more similar to A reduction in the base of the pyramid, due to the reduction of the birth rate, but if there is a reduction in the mortality rate as well, bringing a perspective of an aging population and a future reduction in the number of people in the future. Productive age, which demands higher consumption of electric energy. In parallel, as observed by Tolmasquim (2003), there is an increasing concern for the preservation of the environment, which is an essential concern for man to continue to enjoy the planet. As this problem is directly linked to energy consumption, that is, the need to use renewable energy worldwide is increasing. When it comes to Brazil, there is a consumption of renewable energy above the world average, but the country is very focused on a single source, the hydropower, which can not be said to have zero impact on the environment, in addition, when there is a shortage of this Source, there is a supply problem across the country, making expansion necessary for more renewable sources. From the project area, we have been quoted by several authors throughout the present work, the fact that the Project Management area brings greater efficiency to the companies, by being able to complete within deadlines, costs and estimates stipulated; So the idea is that, in order to stimulate this increase of renewable energy offerings, the project tools can gain greater efficiency in the projects of implantation of power plant, in the case of the present research, Solar Photovoltaic Energy. Therefore, as the auction model is currently used, the present work will treat each auction as a different project, evaluating how much the complexity of each project, measured by size and logistics, influence its sale price and investment. The information used can be found in the public worksheet of CCEE - Electric Energy Trading Chamber. From there it is possible to perceive that these characteristics, which until then not widely researched really bring a degree of influence on the characteristics of described projects.